Profitability and Trend Analysis of Select Retail Companies in India - Chellasamy, P.; Ponsabariraj, N. (Indian Journal of Finance, 2013)
Retailing involves a direct interface with the customer and the coordination of business activities from end to end, right from the concept or design stage of a product or offering, to its delivery and post-delivery service to the customer. The business environment in the last decade has changed the face of every business activity with a paradigm shift in the volume and quality. Retailing is considered as one of the largest industries in India. It has emerged as one of the most dynamic and fast paced industries, with several players entering the market. The Indian retail business is being driven by yearly net profit, operational efficiency, changing lifestyles, and favorable demographic patterns. The retail sector is an important contributor to the development of our economy. An important aspect of the current economic scenario in India is the emergence of organized retailing, which involves a highly competitive environment, a business setup, cost of labour and materials, consumer based products, and so forth. The study aims to analyze the profitability position, overall operating indicator, and trend analysis of selected retail companies in India considering the time period from 2002-03 to 2011-12.